2020
DOI: 10.3390/su12072887
|View full text |Cite
|
Sign up to set email alerts
|

Historical Cloisters and Courtyards as Quiet Areas

Abstract: Searching for renovating and/or constructing quiet areas in historical urban sites, along with the conservation and valorization policies of the tangible and intangible value of historic urban sites are goals that can be combined into a unique sustainable strategy for the preservation of the sense of place and identity of communities as well as their well-being. Historic cloisters and courtyards are examples of such sites. Due to their physical, architectural, environmental and cultural features, they present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Others visit the place several times a year (32), weekly (21), only in spring or summer (9), or monthly (7) (Table 6). The participants' noise sensitivity was also measured using the Weinstein Noise Sensitivity Scale (WNSS) [35][36][37]. The results indicated that Italian and Turkish participants had similar levels of noise sensitivity, with the Turkish sample having a mean value of 4.19 (median = 4.25; dev.st.…”
Section: Questionnairesmentioning
confidence: 99%
See 1 more Smart Citation
“…Others visit the place several times a year (32), weekly (21), only in spring or summer (9), or monthly (7) (Table 6). The participants' noise sensitivity was also measured using the Weinstein Noise Sensitivity Scale (WNSS) [35][36][37]. The results indicated that Italian and Turkish participants had similar levels of noise sensitivity, with the Turkish sample having a mean value of 4.19 (median = 4.25; dev.st.…”
Section: Questionnairesmentioning
confidence: 99%
“…This paper explores the physical and perceptual characteristics of 20 historical sites located inside the old city centre of Naples, in Italy [33][34][35][36], and in the historical Peninsula of Istanbul, in Turkey [37], by analysing the correlations existing among them, identifying the main perceptual dimensions describing these places, and highlighting the resultant differences between the two regions. Great attention has been paid to investigate the importance of the cultural aspects on the restorative potentials.…”
Section: Introductionmentioning
confidence: 99%
“…Based on machine learning simulation, Xiang et al concluded that the shape and layout of building enclosures in common spaces are significantly related to people's emotions (20). Lindal, Weber and Masullo et al believed that the number of turns in architectural outlines and historical elements in the architectural environment, and rich changes in building facades, can arouse people's interest and divert their attention from their daily needs and spiritual content and help them to achieve psychological restoration (21)(22)(23)(24)(25)(26). In addition, there is ample evidence that increases in the quantity, type and color of vegetation in campus landscape spaces and sports fields is significantly related to enhanced psychological restoration (27)(28)(29).…”
Section: Characteristics Of Campus Common Spacesmentioning
confidence: 99%
“…The physical, psychological, and contextual factors [ 9 ], the geometry of the surrounding buildings [ 46 ], the architectural contemporary and historical landscape characteristics [ 47 ], the ecological processes and other environmental factors formulate the acoustic environment and shape the soundscape. All the above information can be quantified, assigned with weights, and incorporated in a composite indicator in order to define aspects of the acoustic environment and attempt to describe the soundscape.…”
Section: Scientific Background: Revisiting Quietnessmentioning
confidence: 99%